FLAVODIIRON2 and FLAVODIIRON4 Proteins Mediate an Oxygen-Dependent Alternative Electron Flow in Synechocystis sp. PCC 6803 under CO2-Limited Conditions . Issue 2 (24th December 2014) - Shimakawa, Ginga; Shaku, Keiichiro; Nishi, Akiko; Hayashi, Ryosuke; Yamamoto, Hiroshi; Sakamoto, Katsuhiko; Makino, Amane; Miyake, Chikahiro
Abstract : Two iron-bound flavidoxin-domain proteins mediate an oxygen-dependent alternative electron flow in the cyanobacterium Synechocystis under CO2 -limited conditions. Abstract: This study aims to elucidate the molecular mechanism of an alternative electron flow (AEF ) functioning under suppressed (CO2 -limited) photosynthesis in the cyanobacterium Synechocystis sp. PCC 6803. Photosynthetic linear electron flow, evaluated as the quantum yield of photosystem II [Y(II) ], reaches a maximum shortly after the onset of actinic illumination. Thereafter, Y(II) transiently decreases concomitantly with a decrease in the photosynthetic oxygen evolution rate and then recovers to a rate that is close to the initial maximum. These results show that CO2 limitation suppresses photosynthesis and induces AEF . In contrast to the wild type, Synechocystis sp. PCC 6803 mutants deficient in the genes encoding FLAVODIIRON2 (FLV2) and FLV4 proteins show no recovery of Y(II) after prolonged illumination. However, Synechocystis sp. PCC 6803 mutants deficient in genes encoding proteins functioning in photorespiration show AEF activity similar to the wild type. In contrast to Synechocystis sp. PCC 6803, the cyanobacterium Synechococcus elongatus PCC 7942 has no FLV proteins with high homology to FLV2 and FLV4 in Synechocystis sp. PCC 6803. This lack of FLV2/4 may explain why AEF is not induced under CO2 -limited photosynthesis in S. elongatus PCC 7942. As the glutathione S -transferase fusion protein overexpressed in Escherichia coli exhibits NADH-dependent oxygen reduction to water, we suggest that FLV2 and FLV4 mediate oxygen-dependent AEF in Synechocystis sp. PCC 6803 when electron acceptors such as CO2 are not available.